1987
DOI: 10.1111/j.1365-2265.1987.tb00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of T4 and T3 Binding Kinetics in the Thyroxine Binding Globulin Abnormality of Australian Aborigines

Abstract: Low serum total T4 associated with subnormal concentrations of thyroxine binding globulin (TBG) has been reported in up to 40% of euthyroid Australian aborigines. It has been suggested that these subjects show both diminished concentration of TBG and reduced TBG affinity for T4 (Sarne et al., 1985). We have compared 12 euthyroid aborigines with low T4 (total T4 44 +/- 5 nmol/l) and aborigines with normal T4 (T4 99 +/- 9 nmol/l, n = 12) using measurements of free T4 and T3 by equilibrium dialysis. TBG was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Early anthropological studies showed that desert-dwelling Aboriginal Australians could maintain reduced metabolic rates without shivering when temperatures drop below 0°C at night [84]. Compared with people of European descent, they also have lower levels of thyroid hormone thyroxine (T4) and reduced affinity for T4-binding globulin, suggesting that selection has targeted thyroid-induced metabolism in Aboriginal Australians, resulting in increased adaptive thermal tolerance [88][89][90][91].…”
Section: Box 2 Genetic Adaptations In Humansmentioning
confidence: 99%
“…Early anthropological studies showed that desert-dwelling Aboriginal Australians could maintain reduced metabolic rates without shivering when temperatures drop below 0°C at night [84]. Compared with people of European descent, they also have lower levels of thyroid hormone thyroxine (T4) and reduced affinity for T4-binding globulin, suggesting that selection has targeted thyroid-induced metabolism in Aboriginal Australians, resulting in increased adaptive thermal tolerance [88][89][90][91].…”
Section: Box 2 Genetic Adaptations In Humansmentioning
confidence: 99%